Investigating Science Learning in Elementary Schools: Class Action Research on SAVI Learning Models - Juhji Juhji; Devi Anggraeni; Teguh Fachmi (Indonesian Journal of Elementary Teachers Education, 2021)
Students' inactivity in learning and teacher inaccuracies in using the model led to low science learning outcomes in elementary school. This investigation aims to analyze students' science learning outcomes through the SAVI model. Class Action Research from Kemmis and Mc. Taggart was used as a research method. Valid science learning test instruments and observation sheets of learning implementation are used as research instruments. The results of the investigation showed an increase in the results of science learning in grade 4 students in elementary school, this can be seen in the percentage of changes in the completion of their learning outcomes. This study provides recommendations for teachers to apply the SAVI model in the classroom learning so that students' science learning outcomes improve.